2009
DOI: 10.1126/science.1165971
|View full text |Cite
|
Sign up to set email alerts
|

Signal Sequences Activate the Catalytic Switch of SRP RNA

Abstract: The signal recognition particle (SRP) recognizes polypeptide chains bearing a signal sequence as they emerge from the ribosome, and then binds its membrane-associated receptor (SR), thereby delivering the ribosome-nascent chain complex to the endoplasmic reticulum in eukaryotic cells and the plasma membrane in prokaryotic cells. SRP RNA catalytically accelerates the interaction of SRP and SR, which stimulates their guanosine triphosphatase (GTPase) activities, leading to dissociation of the complex. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 20 publications
(29 reference statements)
7
77
1
1
Order By: Relevance
“…The 4.5S RNA accelerates binding between Ffh and its membrane-associated receptor FtsY, targeting Ffh-bound nascent polypeptides for secretion by the co-translational pathway (Bradshaw et al, 2009). Here, we present data Fig.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The 4.5S RNA accelerates binding between Ffh and its membrane-associated receptor FtsY, targeting Ffh-bound nascent polypeptides for secretion by the co-translational pathway (Bradshaw et al, 2009). Here, we present data Fig.…”
Section: Discussionmentioning
confidence: 52%
“…FfhFtsY complex formation also stimulates the GTPase activities of both proteins, leading to their dissociation and making them available for additional rounds of protein targeting (Powers & Walter, 1995). Thus, the 4.5S RNA functions as a molecular switch that couples GTP hydrolysis to protein secretion (Bradshaw et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that in cytosolic SRP pathways, the SRP RNA exerts its stimulatory effect on SRP • SR complex assembly only in the presence of cargo or a stimulatory detergent such as Nikkol that partially mimics the effect of the cargo (Bradshaw et al, 2009;Zhang et al, 2009). This led to the proposal that the SRP RNA acts as a molecular linker that turns on the GTPase cycles of SRP and SR in response to signal sequence binding in the M-domain.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously cpSRP54, even though its M-and NG-domains would be prepositioned, cannot efficiently interact with the E. coli FtsY. The stimulatory effect of the SRP RNA and the M-domain of cpSRP54 is highly specific to their homologous receptors, arguing against the first two models in which the origin of the stimulatory effect would be more generic.It was recently shown that in cytosolic SRP pathways, the SRP RNA exerts its stimulatory effect on SRP • SR complex assembly only in the presence of cargo or a stimulatory detergent such as Nikkol that partially mimics the effect of the cargo (Bradshaw et al, 2009;Zhang et al, 2009). This led to the proposal that the SRP RNA acts as a molecular linker that turns on the GTPase cycles of SRP and SR in response to signal sequence binding in the M-domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation